2020
DOI: 10.1080/10615806.2020.1866174
|View full text |Cite
|
Sign up to set email alerts
|

A person-centered perspective on the factors associated with the work recovery process

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…For instance, in a longitudinal study Kinnunen et al (2017) found five stable individual patterns between affective rumination, problem-solving pondering, and lack of psychological detachment that differently related to job demands and mental wellbeing. Similarly, Gillet et al (2020) found four consistent patterns between overcommitment, rumination, and psychological detachment that were associated with different outcomes and work-related stressors in two substudies. Finally, in another longitudinal study, Casper et al (2019) identified six profile combinations between positive and negative work reflection.…”
Section: Conceptual Definitionsmentioning
confidence: 70%
“…For instance, in a longitudinal study Kinnunen et al (2017) found five stable individual patterns between affective rumination, problem-solving pondering, and lack of psychological detachment that differently related to job demands and mental wellbeing. Similarly, Gillet et al (2020) found four consistent patterns between overcommitment, rumination, and psychological detachment that were associated with different outcomes and work-related stressors in two substudies. Finally, in another longitudinal study, Casper et al (2019) identified six profile combinations between positive and negative work reflection.…”
Section: Conceptual Definitionsmentioning
confidence: 70%
“…In Study 3, we directly tested the role of workload as a correlated predictor of membership into the identified profiles on the basis of previous variable-centered results supporting its association with workaholism (Gillet et al, 2018;Huyghebaert et al, 2018a) and psychological detachment (Bennett et al, 2016;Gillet et al, 2020b). Indeed, employees exposed to higher workloads have to work harder to achieve their objectives, making it more likely for them to think about their work obligations when outside of the work settings, thus leading to high levels of workaholism (Schaufeli et al, 2008).…”
Section: Workloadmentioning
confidence: 99%
“…In most applied cases researchers will wish to use LPA on multiple indicators. The were chosen in line with results from Gillet et al (2020). Hence, within sampling error, our analysis will lead to roughly identical conclusions.…”
Section: Example 2: Multivariate Lpa Of Work Recoverymentioning
confidence: 97%
“…In practice, LPA/LCA is also frequently applied to classify persons over a range of conceptually related, but distinct constructs (e.g., J. Bauer & Mulder, 2013;Gillet et al, 2020). In that case, the resulting profiles are mere summaries of persons with similar answer patterns and should not be interpreted as realizations of a latent trait (see section 4.1 on the danger of reification).…”
Section: Steps In Lpa/lcamentioning
confidence: 99%
See 1 more Smart Citation